Dynamics variables phenomenon in the removal efficiency of heavy metals in facultative pond - Aldana, Gerardo; Aiello, Cateryna; Morán, Milmero; Jérez, Oswaldo (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
The purpose of this paper is to determine the removal efficiency of heavy metals in Facultative Ponds. Several variables such as: wind currents, temperature, pH, flowrate and photosynthesis influenced the research. These variables were taken in to account to evaluate removal efficiencies for Copper, Zinc, Chromium and lron, at differents depths in pond. The research was conducted in a series of Stabilization Ponds located in the main campus of the Universidad del Zulia (L.U.Z.). The results point out to the fact that pond's performance influencing removal efficiency was almost similar for the four cations under inquire at depth of 0,40 m. Concentrations appeared higher near the surface compared to those close to the bottom of 2.00 m. Diurnal variations in flowrate affected measured concentration for metals probably due to wind currents which tend to increase concentration values at top level. Removal percentages were: 100% for Copper; 90% for Zinc; 75% for Chromium and, 64% for iron. Concentrations for the four cations were obtained by Atomic Absorption Spectrophotometry (AAS).